Geography and technology - Brunn, Stanley D.; Cutter, Susan L.; Harrington Jr., J. W. (Kluwer Academic Publishers, 2004)
1. Geography and technology interfaces ; 2. Technologies that changed geography ; 3. New geographies with new technologies ; 4. The environment and technology ; 5. The worlds before us